Fraudulent Financial Reporting: An Application of Fraud Pentagon Theory to Association of Southeast Asian Nations Corporate Governance Scorecard - PAMUNGKAS, Imang Dapit; UTOMO, St. Dwiarso (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
This study aims to detect and examine fraudulent financial reporting by applying fraud pentagon theory to all companies implementing the Association of Southeast Asian Nations (ASEAN) Corporate Governance Scorecard in Indonesia. This study has the following objectives: to examine and analyze the effect of financial stability, external pressure, financial target, nature of industry, audit opinion, change of directors, managerial ownership against fraudulent financial reporting. In this research, we use correlation research type. The population of this sample is all sectors of companies listed on the Indonesia Stock Exchange. Using sampling technique in the form of Purposive Sampling Technique applying ASEAN Corporate Governance Scorecard in Indonesia with research period of 2012 to 2016, which produce 30 samples, multiple linear regression analysis using SPSS version 22. The results of this study found that financial stability, managerial ownership has a negative and insignificant effect on fraudulent financial reporting. External pressure, nature of industry has a negative and significant effect on fraudulent financial reporting. Financial Target, Audit Opinion, Change of Directors has a positive and insignificant effect on Fraudulent Financial Reporting.